Webinar: Enhancing investment in soil health and carbon storage: Frontiers for linking finance and carbon accounting - Costa, Ciniro; Mealey, Tim; Bossio, Deborah A.; Nieuwkoop, Martien van; Paustian, Keith; Jirka, Stefan; Harburg, Dan; Salas, William; Donnelly, Aldyen; Reed, Debbie; Henry, Beverley; Bachman, Pamela M; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This event was co-organized by CCAFS-CGIAR, The Nature Conservancy, 4 per 1000 Executive Secretariat, World Bank and the Meridian Institute.